Making maxillary barbels with a proximal‐distal gradient of Wnt signals in matrix‐bound mesenchymal cells. Issue 6 (23rd October 2015) - Figueroa, Francisco; Singer, Susan S.; LeClair, Elizabeth E.
SUMMARY The evolution of specific appendages is made possible by the ontogenetic deployment of general cell signaling pathways. Many fishes, amphibians and reptiles have unique skin appendages known as barbels, which are poorly understood at the cellular and molecular level. In this study, we examine the cell arrangements, cell division patterns, and gene expression profiles associated with the zebrafish maxillary barbel, or ZMB. The earliest cellular organization of the ZMB is an internal whorl of mesenchymal cells in the dermis of the maxilla; there is no epithelial placode, nor any axially‐elongated epithelial cells as expected of an apical ectodermal ridge (AER). As the ZMB develops, cells in S‐phase are at first distributed randomly throughout the appendage, gradually transitioning to a proliferative population concentrated at the distal end. By observing ZMB ontogenetic stages in a Wnt‐responsive transgenic reporter line, TCFsiam, we identified a strongly fluorescent mesenchymal cell layer within these developing appendages. Using an in vitro explant culture technique on developing barbel tissues, we co‐localized the fluorescent label in these cells with the mitotic marker EdU. Surprisingly, the labeled cells showed little proliferation, indicating a slow‐cycling subpopulation. Transmission electron microscopy of the ZMB located these cells in a single, circumferential layer within the barbel's matrix core. Morphologically, these cells resemble fibroblasts or osteoblasts; in addition to their matrix‐bound location, they are identified by their pancake‐shaped nuclei, abundant rough endoplasmic reticulum, and cytoplasmic extensions into the surrounding extracellular matrix. Taken together, these features define a novel mesenchymal cell population in zebrafish, the "TCF+ core cells." A working model of barbel development is proposed, in which these minimally mitotic mesodermal cells produce collagenous matrix in response to ectodermally‐derived Wnt signals deployed in a proximal‐distal gradient along the appendage. This documents a novel mechanism of vertebrate appendage outgrowth. Similar genetic signals and cell behaviors may be responsible for the independent and repeated evolution of barbel structures in other fish species.